Side Effects of Damping Element Insertion in LCL Filter for DC/AC Inverter - Faizal Arya Samman; Ma'arif Hasan; Tirza Damayanti (Institute of Advanced Engineering and Science, 2018)
The negative impacts or side effects of a damper circuit insertion in an LCL passive filter utilized to filter DC/AC inverters output voltage is presented in this paper. For comparative study, this paper discusses two damping configurations, namely series and parallel damping, as well as the LCL filter without damping element. Four criteria are used to explore the impacts of the damper circuits, i.e. their total harmonic distortions (THDs), the output voltage amplitude, the output power and the power efficiency. Theoretically and emphirically shown by previous studies, the damper can indeed reduce the peak resonance frequency of the filter in its frequency response curve. However, in any circumstance, it can potentially reduce the inverters power and efficiency, voltage output amplitude, and cannot improve its THD reduction. The analysis results have shown that the side effects depends also on the load conditions, which are different for each damping circuit configuration.